Review of relative age effects and potential ways to reduce them in sport and education - David Gutiérrez Díaz del Campo (FEADEF, 2013)
Differences on chronological age within a peer/age group are known as Relative Age, and its consecuences as Relative Age Effec (RAE). This article is a review of the most relevant publications in both the educative and sportive contexts. The decision of reviewing both contexts in the same article is based on the existence of many points in common between them. Furthermore when research is made on youth sport, all the participants are at the same time in the educational system. The hypothesis of the origin of RAE and possible solutions are discussed and analysed at the end of the paper. Besides the objective of compiling and analyse what literature says about RAE, this article has the aim of raisig awareness about this problem and wish of intervention in educators and sportive managers.